The diffusion of nationwide ICT innovation and socio-economic context: Case of the Internet - Kim, Dong Han; Park, Min Jae (International Journal of Technological Learning, Innovation and Development, 2020)
The internet has spread more rapidly than any technological innovation in the history of mankind. The purpose of this study is to investigate the time required to reach the inflection point of the internet, which is the innovation diffusion by country, using the time required to reach the saturation rate among various types of information that can be presented by the Bass diffusion model. The Bass model is the model most frequently used in nationwide diffusion studies, because of its simplicity of application and robust theoretical basis. We also examine what socio-economic factors relate to this spreading time. This study then proposes the contexts by socio-economic indexes that can affect internet penetration through decision trees. Based on the analysis, we classified countries into five groups. This study propose a new approach of national classification is introduced in the technology-based innovation policy by utilising the advantages of the two methodologies of the Bass diffusion model and the decision tree.
Keywords: Bass diffusion model; Country classification; Decision tree; ICT diffusion; Internet